Research on Deformation Patterns and Influencing Factors of Ten Pilot Tunnel Pile Method Construction in Large Span Metro Stations - ZHOU Tao (Chengshi guidao jiaotong yanjiu)
［Objective］ To ensure the construction safety of large span metro stations, it is necessary to conduct research on the deformation patterns of the station structure and the influencing factors in the construction process of ten pilot tunnel pile method. ［Method］ With Xihuang Village Station as the engineering background, a numerical model for the construction of ten pilot tunnel pile method in large span stations is established. The patterns of ground settlement law and the pile horizontal deformation patterns at different construction stages are analyzed. The influence pattern of the three factors, namely the excavation sequence of pilot tunnels, the staggered distance of pilot tunnel excavations, and the construction sequence of arch closing, on the ground settlement is studied. ［Result & Conclusion］ The construction of the upper pilot tunnels and the middle pilot tunnels above the station has a greater impact on the ground settlement. The ground settlement patterns of each construction stage all conform to the normal distribution. The maximum settlement locates at the center line of the station，and the ground settlement caused by the pilot tunnel construction and the arch closing construction accounts for 74.7% of the total settlement. After the excavation of the soil on the second basement level of the station, the horizontal restraint of the piles is sharply weakened, resulting in increased horizontal deformation of the piles. The ground settlement caused by the first excavation of the lower pilot tunnels is relatively small. As the staggered distance of the pilot tunnel excavation increases, the maximum ground settlement gradually decreases. The construction sequence of first excavating the side arch closings and then successively excavating the middle arch closings causes the least ground settlement.